2021
DOI: 10.1083/jcb.202005219
|View full text |Cite
|
Sign up to set email alerts
|

A septin GTPase scaffold of dynein–dynactin motors triggers retrograde lysosome transport

Abstract: The metabolic and signaling functions of lysosomes depend on their intracellular positioning and trafficking, but the underlying mechanisms are little understood. Here, we have discovered a novel septin GTPase–based mechanism for retrograde lysosome transport. We found that septin 9 (SEPT9) associates with lysosomes, promoting the perinuclear localization of lysosomes in a Rab7-independent manner. SEPT9 targeting to mitochondria and peroxisomes is sufficient to recruit dynein and cause perinuclear clustering. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 114 publications
(159 reference statements)
0
22
0
Order By: Relevance
“…(ii) Nevertheless, LIR motifs can be found in autophagy-related, but non autophagy-receptor proteins that play role in autophagosome transport or maturation [ 33 ]. A recent study revealed that another septin from the SEPT3 subgroup, septin-9 acts as an adaptor protein by recruiting dynein-dynactin to lysosomes and enhances their retrograde transport during stress [ 82 ]. Septin-9 also binds a kinesin [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Nevertheless, LIR motifs can be found in autophagy-related, but non autophagy-receptor proteins that play role in autophagosome transport or maturation [ 33 ]. A recent study revealed that another septin from the SEPT3 subgroup, septin-9 acts as an adaptor protein by recruiting dynein-dynactin to lysosomes and enhances their retrograde transport during stress [ 82 ]. Septin-9 also binds a kinesin [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a local disruption of microtubules and the axonal actin-spectrin cytoskeleton, phenotypes that are accompanied by an increase in total and phosphorylated tau protein, have been recently found in JIP3 KO iPSC-derived cortical glutamatergic neurons, phenotypes that are further aggravated by the co-depletion of its paralog JIP4 (Rafiq et al 2020). A tight link between the retrograde dynein-driven transport of lysosomes and the cytoskeletal scaffold protein Septin-9 has been reported in non-neuronal cells (Kesisova et al 2020). Future studies are thus needed to define the exact roles of the various forms of the axonal cytoskeleton in the anterograde and retrograde movement of (pre)lysosomes and autophagosomes.…”
Section: Matur Ati On and Re Trog R Ade Tr An S P Ort Of Endosome S A...mentioning
confidence: 94%
“…A tight link between the retrograde dynein‐driven transport of lysosomes and the cytoskeletal scaffold protein Septin‐9 has been reported in non‐neuronal cells (Kesisova et al . 2020). Future studies are thus needed to define the exact roles of the various forms of the axonal cytoskeleton in the anterograde and retrograde movement of (pre)lysosomes and autophagosomes.…”
Section: Maturation and Retrograde Transport Of Endosomes And Autopha...mentioning
confidence: 99%
“…In addition, a link between septins and JNK may exist in the environment of MTs. Indeed, septins are scaffold partners of MAPs on MTs, including the structural MAP4, the tubulin-deacetylase HDAC6 (for review [180]), the dynein/dynactin motor complex [181] and maybe the +TIPs CLIP-170 and MCAK [158]. Also, SEPT9 mediates a dyneindependent retrograde transport of lysosomes, and this property is enhanced upon arsenite stress, a well-known JNK activator.…”
Section: Jnk and Septinsmentioning
confidence: 99%